Role of Organisational Behaviour (OB) to Enhance Productivity in a Public Sector Enterprise - Javed, I. K.; Jahanzaib, M.; Wasim, A.; Salman, H. (Journal of Advanced Research in Business and Management Studies, 2020)
Low productivity in manufacturing setups is traceable to poor employee performance, employee absenteeism, low turnover and motivation. This research aims to explore the relationship of motivation, absenteeism and employees’ turnover to the labour productivity in public sector enterprises. The data for this study was collected in two stages. Firstly, the data from lower employees was collected followed by data collection from the staff and officers in second stage. A total number of 300 participants contributed in this research. Data was found normally distributed and therefore pearson correlation and regression analysis were used for analysis. The survey results indicate that motivation has strong positive relationship with the labour productivity while absenteeism and employee turnover have negative associations to the labour productivity. Furthermore, motivation has negative association with employee turnover and absenteeism. The study also concludes that absenteeism and turnover has positive association. In addition to survey, guidelines have been developed to enhance labour productivity in public enterprises.